ASUHAN KEPERAWATAN GERONTIK DENGAN INTERVENSI PEMBERIAN JUS SIRSAK UNTUK MENURUNKAN KADAR ASAM URAT DI PANTI WERDHA KASIH AYAH BUNDA TANGERANG 2023 - Dewi Puji Astuti; Siti Robeatul Adawiyah; Siti Rahayu; Rina Puspita Sari (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Based on the Ministry of Health (2019) Indonesia is entering an Aging Population period, where there is an increase in life expectancy followed by an increase in the number of elderly people. An increase in the number of elderly population will be a problem if the elderly have health problems. The most common health problems are non-communicable diseases such as gout. High uric acid levels can cause joint pain. There are two ways to reduce uric acid, pharmacological and non-pharmacological. Non-pharmacological can be done by giving soursop fruit juice. The content of vitamin C in soursop fruit juice can help reduce uric acid levels. Purpose: The purpose of this writing is to provide an overview of the results of nursing care for Gout Arthritis patients in reducing uric acid levels by administering soursop fruit juice. Method: Case study by conducting nursing care from assessment to evaluation. Results: Based on the implementation results on Mr. N with the application of soursop juice therapy for 7 days it was found that uric acid levels on the first day were 9.8 mg/dl dropped to 8.3 mg/dl so that health maintenance diagnoses were not effectively handled, and it can be concluded that there is a change towards improvement, this indicates There is an effect of giving soursop fruit juice on decreasing uric acid levels.